Behaviour Disorders of Childhood and Adolescence: Implications for Education in Nigeria - Nungala Usman Isaac (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2024)
Behaviour disorders in childhood and adolescence are a growing concern in Nigeria, with significant implications for the educational system. This study examines the prevalence, characteristics, and impact of behaviour disorders, such as Attention Deficit Hyperactivity Disorder (ADHD), Conduct Disorder, and Anxiety Disorders, on students' academic performance, social relationships, and overall well-being. A comprehensive review of existing literature and empirical data from Nigerian schools reveals a lack of awareness, inadequate support services, and insufficient teacher training in addressing behaviour disorders. The findings highlight the need for a multidisciplinary approach to address these issues, including: teacher training on behaviour management and support strategies, integration of mental health services into school systems, promotion of inclusive education practices, encouragement of parental involvement and community engagement and development and implementation of evidence-based interventions. The study recommends policy changes and implementation of support services to address behaviour disorders in Nigerian schools. By addressing behaviour disorders in childhood and adolescence, Nigeria can improve educational outcomes, reduce social and emotional difficulties, and promote a healthier and more productive society.